2014
DOI: 10.5194/acp-14-2363-2014
|View full text |Cite
|
Sign up to set email alerts
|

The impact of the chemical production of methyl nitrate from the NO + CH<sub>3</sub>O<sub>2</sub> reaction on the global distributions of alkyl nitrates, nitrogen oxides and tropospheric ozone: a global modelling study

Abstract: Abstract. The formation, abundance and distribution of organic nitrates are relevant for determining the production efficiency and resident mixing ratios of tropospheric ozone (O 3 ) on both regional and global scales. Here we investigate the effect of applying the recently measured direct chemical production of methyl nitrate (CH 3 ONO 2 ) during NO x recycling involving the methyl-peroxy radical on the global tropospheric distribution of CH 3 ONO 2 and the perturbations introduced towards tropospheric NO x a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
52
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(60 citation statements)
references
References 70 publications
7
52
0
1
Order By: Relevance
“…The branching ratio between reactions and (combined where relevant with the branching ratio for formation of the specific RO2· isomer) represents the yield of RONO 2 , referred to as α . For the species considered here, α increases from <1% for methyl nitrate (CH 3 ONO 2 ; Flocke et al, ) to ≈2% for ethyl nitrate (C 2 H 5 ONO 2 ; Ranschaert et al, ) to >3% for propyl nitrate (C 3 H 7 ONO 2 ; Atkinson et al, )—although precise measurement of α remains an important source of uncertainty in atmospheric RONO 2 budgets (Butkovskaya et al, ; ; Khan et al, ; Nault et al, ; Williams et al, ). While reaction has no net impact on available atmospheric NO x , reaction can recycle NO x , temporarily sequester NO x , or permanently remove NO x from the atmosphere, depending on the lifetime and fate of the RONO 2 produced (Fisher et al, ; Perring et al, ).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…The branching ratio between reactions and (combined where relevant with the branching ratio for formation of the specific RO2· isomer) represents the yield of RONO 2 , referred to as α . For the species considered here, α increases from <1% for methyl nitrate (CH 3 ONO 2 ; Flocke et al, ) to ≈2% for ethyl nitrate (C 2 H 5 ONO 2 ; Ranschaert et al, ) to >3% for propyl nitrate (C 3 H 7 ONO 2 ; Atkinson et al, )—although precise measurement of α remains an important source of uncertainty in atmospheric RONO 2 budgets (Butkovskaya et al, ; ; Khan et al, ; Nault et al, ; Williams et al, ). While reaction has no net impact on available atmospheric NO x , reaction can recycle NO x , temporarily sequester NO x , or permanently remove NO x from the atmosphere, depending on the lifetime and fate of the RONO 2 produced (Fisher et al, ; Perring et al, ).…”
Section: Introductionmentioning
confidence: 97%
“…Using aircraft observations from the PEM‐Tropics campaigns, Neu et al () inferred a constant ocean flux of 0.35 Tg N yr −1 , mainly from the tropical Pacific with a small contribution from the Southern Ocean. However, the model used in their study did not include atmospheric production of RONO 2 via reactions , which likely exaggerated the size of the ocean source (Williams et al, ). The Neu et al () estimate was also hampered by the limitations of the aircraft data available at the time, including a lack of seasonal information and particularly large uncertainties for the Southern Ocean, where only one flight leg crossed south of 45°S.…”
Section: Introductionmentioning
confidence: 99%
“…The proposed origin of the methyl nitrate (Williams et al, 2014) is shown in Reaction (R14) and formaldehyde, which is formed as a major by-product is shown in Reaction (R15) (Singh et al, 1995: Warneck andZerbach, 1992).…”
Section: Pan Preparationmentioning
confidence: 99%
“…In that case, the difference between the retrieved CH 4 column and the a priori CH 4 column from the chemical transport model TM5 (Williams et al, 2013(Williams et al, , 2014 reflects the light-path effect of aerosols and clouds on the observations due to shielding and photon path enhancement by multi-scattering (Vidot et al, 2012). For the subsequent retrieval of CO, we use the retrieved nonscattering CH 4 column to provide a first estimate for the cloud height.…”
Section: Retrieval Settingsmentioning
confidence: 99%
“…Thereby, it supplies CO vertical column densities that we transformed to column averaged mixing ratios by calculating the dry-air column from the surface pressure at the station sites. The TCCON instruments measure in the same spectral range as SCIAMACHY and provide the vertical column densities of trace gases including CO with high precision (Wunch et al, 2010(Wunch et al, , 2011. Because of the lack of profile information, it is not possible to apply averaging kernels, and NDACC/TCCON data must be compared directly with the SCIAMACHY cloudysky retrievals.…”
Section: Ground-based Fourier Transform Spectrometers (Ndacc/tccon)mentioning
confidence: 99%